Analysis on acoustic performance of floating raft vibration isolation system with liquid tank - Zhiyang LEI; Kun DU; Chongjian WU; Zhigang CHEN; Xiaojie YAN; Jun LIU (Zhongguo Jianchuan Yanjiu, 2022)
ObjectiveThis paper aims to establish a dynamic model of a floating raft vibration isolation system with a liquid tank in order to study the mass effect of the liquid medium, tank form, structural stiffness and loading rate on acoustic performance. MethodsA floating raft system with a cuboidal or cylindrical liquid tank is taken as the research object, and a fluid-structure coupling finite element dynamic model is established. The dynamic force transmission rate and power flow are then used to evaluate the acoustic performance of the system. The influence of the mass effect of the liquid medium, tank form, structural stiffness and loading rate of tank volume on the acoustic performance of the floating raft system are analyzed.ResultsThe results show similar laws obtained through the calculation and analysis of the floating raft system with two types of tanks. The structural stiffness of the tank affects the mass effect of the liquid medium in the tank to a certain extent. ConclusionsIf full advantage is to be taken of the liquid mass effect in the tank with a large loading rate to improve the acoustic performance of the floating raft system, the design of the liquid tank and raft structure must have sufficient stiffness. In addition, under the condition that the floating raft structure has sufficient stiffness, its acoustic performance will improve significantly as the tank loading rate increases in the relevant low frequency range.